Performance Studies of Multimedia Traffic in CDMA Cellular Network - Balan Nair, Madhavan (1999)
The current generation of wireless cellular network is mostly used for voice communication. Although data services such as short message services (SMS) are available, voice communication still takes precedence. However, in the near future, it is anticipated that wireless communication is expected to handle multimedia traffic that is currently available on land networks. Multimedia traffic includes video services such as real time video and audio, voice services and data services similar to the ones available in the Internet. The cellular network carrying multimedia traffic is analysed in a single cell where Code Division Multiple Access (CDMA) protocol is used for users to access the network simultaneously. The study is analysed for the reverse link communication, i. e., communication between the user and the base station. CDMA is used because of its merits in minimising the effect of interference, increasing cell capacity and high security features compared to other access technologies. The model inputs include co- channel interference, signal to noise ratio, bit error rate requirements, number of users, the channel access priority and threshold. Suitable assumptions to enable simulation are made. The model is simulated to see the impact of complementing data traffic along with voice and video traffic. The model is also simulated for synchronous transmission and asynchronous transmission of packets. The results shows that data traffic can be successfully complemented along with voice and video traffic without significantly degrading voice and video delay. Data traffic can tolerate delay but is loss sensitive. Data traffic delay can be used without suffering any loss, even by reducing the data access priority. The model also compared the effects of synchronous and asynchronous transmission. Synchronous transmission indicated an overhead in packet delay compared to asynchronous transmission. It is concluded from the work that voice, video and data traffic can be served in a cell simultaneously with asynchronous transmission. A higher bandwidth can assure a higher number of multimedia users in a asynchronous CDMA cellular network. The model will serve as a useful design tool.